2019
DOI: 10.1161/strokeaha.118.024096
|View full text |Cite
|
Sign up to set email alerts
|

Deferral of Consent in Acute Stroke Trials

Abstract: Background and Purpose— The ESCAPE trial (The Endovascular Treatment for Small Core and Anterior Circulation Proximal Occlusion With Emphasis on Minimizing CT to Recanalization Times) was a multicentre, randomized controlled trial of endovascular thrombectomy versus standard care for patients with acute ischemic stroke that allowed patients to be enrolled with deferred consent. We investigated the knowledge and opinions of these patients or their authorized third parties about the consent process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 13 publications
1
50
0
Order By: Relevance
“…Their work also revealed that delayed consent allowed surrogates to express a sense that they could understand trial information better than if it was presented earlier when the context was more stressful, findings applicable to patients themselves faced with potential decision making in critical illness [63]. However, it should be noted that public acceptance of the deferred consent process has not been universally consistent, and further work is justified to understand the patient and legally authorized representative’s perspectives on these issues is warranted [70]. It is possible that there may be disconnect between how respondents felt about deferred consent in theory and how they perceived the process in the real world [70].…”
Section: Discussionmentioning
confidence: 99%
“…Their work also revealed that delayed consent allowed surrogates to express a sense that they could understand trial information better than if it was presented earlier when the context was more stressful, findings applicable to patients themselves faced with potential decision making in critical illness [63]. However, it should be noted that public acceptance of the deferred consent process has not been universally consistent, and further work is justified to understand the patient and legally authorized representative’s perspectives on these issues is warranted [70]. It is possible that there may be disconnect between how respondents felt about deferred consent in theory and how they perceived the process in the real world [70].…”
Section: Discussionmentioning
confidence: 99%
“…, However, the first published study to ask acute stroke trial participants about their attitudes towards deferred consent found that respondents were overwhelmingly opposed. 3 What could account for the discrepancy between that response, and those of SPOTLIGHT participants? The literature suggests that the severity of illness The main limitation of the present study is its small sample size, reflecting both the small size of SPOTLIGHT (50 patients), and a low response rate (20%) for this substudy.…”
Section: Discussionmentioning
confidence: 99%
“…Postponing consent seems tolerated by patients and their relatives in several clinical studies and trials [58][59][60][61][62][63][64][65]. However, a substudy of the ESCAPE trial (the Endovascular Treatment for Small Core and Anterior Circulation Proximal cOcclusion with Emphasis on Minimizing CT to Recanalization Times) showed that the majority of patients or their representatives disagreed with the use of deferred consent [66]. Yet, none of the patients enrolled with deferred consent in this trial withdrew consent later, and patients agreed with the conditions used to justify deferred consent procedures.…”
Section: Deferral Of Consentmentioning
confidence: 99%